miR-4454 Promotes Hepatic Carcinoma Progression by Targeting Vps4A and Rab27A - Haoming Lin (Hindawi Limited, 2021)
Hepatocellular carcinoma (HCC) has high morbidity and mortality. MicroRNAs (miRNAs), which could be regulated by cancer-derived exosomes, play critical regulatory roles in the initiation and development of cancer. However, the expressions, effects, and mechanisms of abundant miRNAs regulated by HCC cancer-derived exosomes in HCC remain largely unclear. Exosomes of HepG2 cells under heat shock, TGF-β1, doxorubicin, acid and hypoxia/reoxygenation (H/R) conditions, and exosomes were successfully identified by transmission electron microscopy and Western blot analysis. The identified exosomes were then applied to evaluate the miRNA expression profiles by RNA sequencing. Mechanically, we discovered that doxorubicin was upregulated, TGF-β1 downregulated the expressions of Vps4A, Rab27A, Alix, and Hrs in HepG2 cells and exosomes, and Vps4A and Rab27A, as target genes for miR-4454, could also be downregulated by miR-4454. Functionally, we revealed that miR-4454 inhibitor and miR-4454 inhibitor-mediated exosomes could markedly suppress proliferation, migration, invasion, and vascularization and accelerate cycle arrest, apoptosis, and ROS of HepG2 cells. This study provided many potential HCC cancer-derived exosome-mediated miRNAs in HCC under 5 different stimulus conditions. Meanwhile, we certified that miR-4454 in exosomes could provide a novel and effective mechanism for HCC function.